L’assurance automobile au Québec : une évaluation du nouveau régime - Brouillette, Yves (Assurances)

(untitled) (HEC Montréal, 1984)
Mr. Yves Brouillette looks at how well the Quebec Régie d’assurance automobile has carried out the tasks defined in the no-fault legislation. He notes that private enterprise might well have produced the same results, but on the whole the new system has been beneficial, even if the management costs have been considerably above those forecast. The Régie has been able to take advantage of an unusual situation in the field of automobile insurance, resulting from a substantial decrease in the number of accidents together with high investment returns. According to the author, on the whole the automobile insurance reform has given a positive result.